Beta-strength and anti-neutrino spectra from total absorption spectroscopy of a decay chain 142Cs→142Ba→142La - Wolińska-Cichocka Marzena; Rasco B. Charles; Rykaczewski Krzysztof P.; Brewer Nathan T.; Stracener Daniel; Grzywacz Robert; Gross Carl J.; kowska Aleksandra Fijał; Goetz K. Callie; Karny Marek; King Toby; Go Shintaro; et al. (EPJ Web of Conferences, 2017)
Beta decays of mass A = 142 isobaric chain starting from 142Cs have been investigated by means of Modular Total Absorption Spectrometer (MTAS) and on-line mass separation at Oak Ridge National Laboratory. The beta strength distribution derived for 142Cs decay from MTAS spectra is showing significant differences in β-feeding pattern when compared to the values listed at nuclear databases. MTAS results are shifting the associated anti-neutrino energy spectrum towards lower energies. A decay pattern deduced for 142Ba is similar to earlier reported results.